2016
DOI: 10.3346/jkms.2016.31.8.1208
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Analysis of ATRX, IDH1 and p53 in Glioblastoma and Their Correlations with Patient Survival

Abstract: Glioblastoma (GBM) can be classified into molecular subgroups, on the basis of biomarker expression. Here, we classified our cohort of 163 adult GBMs into molecular subgroups according to the expression of proteins encoded by genes of alpha thalassemia/mental retardation syndrome X-linked (ATRX), isocitrate dehydrogenase (IDH) and TP53. We focused on the survival rate of molecular subgroups, depending on each and various combination of these biomarkers. ATRX, IDH1 and p53 protein expression were evaluated immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
3
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 18 publications
3
64
3
6
Order By: Relevance
“…The various studies showed the IDH1 positivity at the range of 11% -54%. 17,18 Our study correlated IDH1 expressionwith clinicopathological parameters and found higher expression of IDH1 in adults (64%) as compared to paediatric patients (33%) which was accordance with the studies of Jaiswal et al (2018), Pollack et al (2011) and Bleeker et al (2009). These studies observed a higher degree of IDH-1 expression in adults (53%-68%) than in paediatric group (20% -36%).…”
Section: Discussionsupporting
confidence: 91%
“…The various studies showed the IDH1 positivity at the range of 11% -54%. 17,18 Our study correlated IDH1 expressionwith clinicopathological parameters and found higher expression of IDH1 in adults (64%) as compared to paediatric patients (33%) which was accordance with the studies of Jaiswal et al (2018), Pollack et al (2011) and Bleeker et al (2009). These studies observed a higher degree of IDH-1 expression in adults (53%-68%) than in paediatric group (20% -36%).…”
Section: Discussionsupporting
confidence: 91%
“…Variants of PTEN were seen exclusively in GBM 1 and 5, while variants of PKHD1 were seen in GBM 1, 4 and 6 ( Figure 2). Only GBM 3 and 4 had variants of the IDH gene ( Figure 2), which correlates with the pathology data as both of these samples expressed the mutant protein IDH1 variant R132H (Table 1), which is associated with a better response to treatment (12). GBM 3 was the only sample to have variants of the PIK3R1 gene, while GBM 5 was the only sample to have variants of the RB1, PIK3CA and CDKN2A genes ( Figure 2).…”
Section: Selection Of Mutated Genes For Personalisationsupporting
confidence: 68%
“…A study into the effects of changes in growth control genes on patient survival supports the importance of isocitrate dehydrogenase (IDH) 1 mutations in glioblastoma [12]. In this study, mutated IDH1 was associated with better survival rates, as was reduced alpha thalassemia/mental retardation syndrome X-linked (ATRX) expression and/or lower expression of TP53 [12]. The possibility of PTEN as a biomarker for GBM is supported by Han et al, who conducted a meta-analysis of PTEN mutation and glioma survival rates, concluding that PTEN mutation is associated with poor prognosis [13].…”
Section: Introductionmentioning
confidence: 97%
“…To determine the performance of this online tool, 53 previously published GBM prognostic factors collected as the procedure shown in Figure S1 and then they were evaluated in OSgbm (Table 2, Figure 1) (Sano et al, 1999;Hung and Howng, 2003;Heimberger et al, 2005;Aaberg-Jessen et al, 2009;Shirai et al, 2009;Pu et al, 2011;Cui et al, 2013;De Tayrac et al, 2013;Lee et al, 2013;Rosati et al, 2013;Wang et al, 2013;Wu et al, 2013;Bai et al, 2014;Han et al, 2014;Meng et al, 2014;Olmez et al, 2014;Zupancic et al, 2014;Maris et al, 2015;Moutal et al, 2015;Yan et al, 2015;Zhao et al, 2015;Chaurasia et al, 2016;Nduom et al, 2016;Steponaitis et al, 2016;Steponaitis et al, 2016;Zhang et al, 2016a;Zhang et al, 2016b;Deng et al, 2017;Dong et al, 2017;Ge et al, 2017;Han et al, 2017;Haynes et al, 2017;Huang et al, 2017;Li et al, 2017;Luo and Zhuang, 2017;Ma et al, 2017;Roy et al, 2017;Wu et al, 2017;Zhang et al, 2017;…”
Section: Validation Of Previously Reported Gbm Prognostic Biomarkersmentioning
confidence: 99%